Antebellum posthuman : race and materiality in the mid-nineteenth century - Ellis, Cristin, 1978- (Fordham University Press, 2018)
"Antebellum Posthuman exposes the volatility of "the human"--torn between liberalism and empiricism--in the 1850s and traces the emergence of an antislavery materialism in antebellum literature. Placing race at the root of posthumanism's intellectual history, this study also examines the conflict between liberalism and materialism in critical theory today"--